Parental Support for Teenagers with Unwanted Pregnancy - Pertiwi, Nur Fitri Ayu; Sari, Yulia; Sukamti, Sri (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Unwanted pregnancies in adolescents account for 11% of total births globally. The long-term impacts of unwanted pregnancies in adolescents vary. Community support is needed for adolescents in dealing with pregnancy until becoming parents. Adolescents who experience unwanted pregnancies have not prepared for their pregnancies so they need support from their parents and the environment to minimize short-term and long-term impacts. The sample of this study was adolescents who experienced unwanted pregnancies who were selected through purposive sampling techniques based on predetermined inclusion and exclusion criteria. The main informants in this study were 5 adolescents who experienced unwanted pregnancies. Additional informants were parents, health cadres, and midwives. Adolescents greatly need the role of the community in supporting adolescents with unwanted pregnancies. Communities that support pregnancies that have already experienced unwanted pregnancies can minimize physical and psychological complications that may occur in adolescents. Adolescents who experience unwanted pregnancies can minimize short-term impacts with community support.